Isolasi dan Identifikasi Senyawa (-)-Asam Usnat dari Lichen Usnea sp. serta Aktivitas Sitotoksiknya terhadap Sel Murine Leukemia P388 - MAULIDIYAH MAULIDIYAH; THAMRIN AZIS; SITTI HADIJAH SABARWATI; MUHAMMAD NURDIN (Fakultas Farmasi Universitas Pancasila, 2015)
Lichen is a symbiotic organism composed by algae and fungi that already known produces spesific secondary metabolites having bioactivities. The aim of this study were to isolate and determine the structure of secondary metabolites of Lichen Usnea sp. and to examine the cytotoxic activity against murine leukemia P388 cells. Isolation was carried out by utilizing colom chromatography using silica gel 60 stationary phase with eluent mixtures of n-hexane and ethyl acetate in a gradient elution. Isolates compounds were identified using UV-Vis spectroscopy, IR, 1H-NMR and 13C-NMR. The identification result obtained was (-)-usnic acid compound with molecular weight (MW) of 344 g/mol, needle-shaped yellow crystals. Test results cytotoxic compound of (-)-usnic acid against murine leukemia P388 cells were derived IC50 5.738 ± 0.61 µg/mL.